Atmospheric Dispersion Analysis for Expected Radiation Dose due to Normal Operation of RSG-GAS and RDE Reactors - P.M. Udiyani; S. Kuntjoro; G.R. Sunaryo; H. Susiati (Atom Indonesia, 2018)
BATAN is planning to build an experimental power reactor, the RDE, to complement the RSG-GAS reactor that is already operating in the Serpong Nuclear Zone (KNS). The experimental power reactor is an HTGR (high-temperature gas-cooled reactor) with 10 MWt power, while the RSG-GAS is a pool-type water-cooled reactor with 30 MWt power. According to standard regulatory practices, under normal operating conditions of the plant, radiological assessment of atmospheric releases to the environment and assessment of public exposures are considered essential. The purpose of this study is to estimate the dose acceptance in Serpong Nuclear Zone (KNS) after operate the RDE operates in KNS-2. To assess the doses, the PC-CREAM 08 computer code was used. It uses a standard Gaussian plume dispersion model and composes a suite of models and data for estimation of the radiological impact assessments of routine and continual discharges from a nuclear reactor. The input data include sourceterm from the RDE and the RSG-GAS, a stack the height of 60 m annual radionuclides release, meteorological data from the Serpong local meteorological station, and agricultural products data from Serpong site. Results show that the highest individual dose in the area around KNS for adults is 6.16×10-3 mSv/y in the S (South) direction and 300 m distance from the stack of RSG. The highest collective dose around KNS within 3 km radius is 6.37×10-3 man-Sv/yr. The results show that the radiological impact of the KNS on the critical groups of public and the individual effective doses satisfy the limits given by the Nuclear Regulatory Agency of Indonesia (BAPETEN). The operation of RDE in KNS-2 does not add significantly to acceptance radiation dose in the environment in KNS. It can also be concluded that the estimated effective doses are lower than the dose constraint of 0.3 mSv/y associated with this plant.